The Effect of Work Environment and Work Motivation on Employee Job Satisfaction at Perumda Air Minum Tugu Tirta Malang - Rosul, Aulia Safaat; Malik, Nazaruddin; Irawati, Sandra (Universitas Muhammadiyah Malang, 2023)
The purpose of this study was to determine the effect of work environment and work motivation on the job satisfaction of employees of Perumda Air Tugu Tirta Malang City. This research uses explanatory research with a quantitative approach. The intended respondents were employees of Perumda Air Tugu Tirta Malang City, totaling 76 respondents who were obtained from distributing questionnaires as primary data. Data analysis techniques used the classical assumption test, multiple linear regression analysis, and hypothesis testing using the SPSS version 26 computer program. The results showed that the work environment has a positive and significant influence on job satisfaction. Work motivation has a positive and significant influence on job satisfaction. Work environment and work motivation together have a significant influence on job satisfaction.